2001
DOI: 10.1111/j.0014-3820.2001.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection for Grazer Resistance to Toxic Cyanobacteria: Evolution of Phenotypic Plasticity?

Abstract: We studied the selection response of the freshwater grazing zooplankter, Daphnia galeata, to increased abundance of cyanobacteria in its environment. Cyanobacteria are a poor-quality and often toxic food. Distinct genotypes of D. galeata were hatched from diapausing eggs extracted from three time horizons in the sediments of Lake Constance, Europe, covering the period 1962 to 1997, a time of change in both the prevalence of planktonic cyanobacteria and levels of phosphorus pollution. We assessed whether the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
208
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(229 citation statements)
references
References 38 publications
(42 reference statements)
15
208
3
1
Order By: Relevance
“…Lastly, the lack of congruence between field and laboratory results could be related to the recently documented ability of Daphnia to adapt to the presence of toxic cyanobacteria in their diet (Hairston et al 2001;Gustafsson and Hansson 2004;Sarnelle and Wilson 2005). Specifically, D. pulicaria genotypes isolated from lakes with abundant cyanobacteria are better able to grow on a diet of 100% toxic M. aeruginosa than genotypes from lakes with few cyanobacteria (Sarnelle and Wilson 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the lack of congruence between field and laboratory results could be related to the recently documented ability of Daphnia to adapt to the presence of toxic cyanobacteria in their diet (Hairston et al 2001;Gustafsson and Hansson 2004;Sarnelle and Wilson 2005). Specifically, D. pulicaria genotypes isolated from lakes with abundant cyanobacteria are better able to grow on a diet of 100% toxic M. aeruginosa than genotypes from lakes with few cyanobacteria (Sarnelle and Wilson 2005).…”
Section: Discussionmentioning
confidence: 99%
“…All of the above suggest that dominance of a phytoplankton assemblage by cyanobacteria may interfere with the ability of Daphnia to suppress total phytoplankton biomass, as has been suggested many times (Sommer et al 1986;Benndorf and Henning 1989;Ghadouani et al 2003). Recent studies indicate that Daphnia may adapt to tolerate cyanobacteria in the diet (Hairston et al 2001;Gustafsson and Hansson 2004;Sarnelle and Wilson 2005), but the significance of these findings with respect to Daphnia control of cyanobacteria has yet to be determined.…”
mentioning
confidence: 87%
“…Recently, it has been shown that the ecological relationship between zooplankton grazers and toxic algae is closely shaped by their evolutionary history (Hairston et al, 1999(Hairston et al, , 2002Colin and Dam, 2002a). Freshwater studies have shown that populations of Daphnia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater studies have shown that populations of Daphnia sp. from lakes where toxic cyanobacteria have bloomed for generations have evolved resistance to the toxic algae (Gilbert, 1990;Hairston et al, 1999;Hairston et al, 2002). Resistance has enabled the Daphnia to feed and grow at higher rates in the presence of the toxic cyanobacteria than conspecifics never exposed to the toxic algae.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated increased behavioral plasticity in response to predator kairomones, and order of magnitude higher genetic differentiation for the trait than for neutral markers, consistent with a strong role for selection as the driver of rapid, directional changes. Another example demonstrated evolution of resistance to toxic food sources (cyanobacteria) through a reduction in phenotypic plasticity over time (Hairston et al, 2001). In a similar way, combining molecular biology and genomics with paleolimnology may test hypotheses about adaptation in populations exposed to severe metal contamination (Pollard et al, 2003).…”
Section: Bd Eads Et Almentioning
confidence: 99%